(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Boletim Contexto is one of publications of the Associação Brasileira de Ciências do Comportamento, which aims to propagate Behavior Analysis as well as news regarding the association. The diversity of its names, authors and texts throughout its 28 years suggest that it is a cultural practice that evolved and may have had distinct functions in the Brazilian Behavior Analysis. With the objective of evaluating the functions that the Boletim had along its history, a comprehensive review of all its texts, including 42 numbers and blog posts until December of 2020, was conducted. Through historiographic analysis, the Boletim’s history was divided into six distinct periods, each of them characterized by specific functions. The findings may aid the comparison and interlocution with other studies that evaluate the institutionalization and development of Brazilian Behavior Analysis, as well as other publications of the association.